The Image as Language: The Creation and the Use of the Visual Message by Young University Students in Their Communicative Social Activity - Ramón-Verdú, Alfredo; Villalba-Gómez, José Víctor (Frontiers in Psychology, 2022)
Visual language, taken from the creation and reception of images perspective, is ever-present in mediatized societies. With an interest in knowing what the experience of this is, a study is carried out in a university context, in the Faculty of Education in the University of Murcia, with the participation of 321 young students. The main objective of this study is to delve into the visual message, as a universal language in its productive and interpretative aspects, within a context marked by technology and the large-scale creation and use of images. The investigation is carried out by starting with a typical target performance, individual, objective questionnaire which included three dimensions: the use of photographs, the use of graphic images and the level of reflection and veracity of the image. A Principal Components Analysis is carried out (PCA), which, after the Oblimin rotation, gives rise to a new conceptual organization, based on the underlying variables. The data shows significant differences depending on the educational interests, a steady decrease in the use of images as ages increase, as well as less use of the image as a language among male participants. Males also make less requests for permission and transfer of permission, for the use of their own image by third parties. There is also evidence of a greater social value given to the image by females, as well as greater reflection and questioning of the message in the over thirties, also by females.